2020
DOI: 10.3390/cancers12020524
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Biological Implications of Modified Levels of Cytokines in Chronic Lymphocytic Leukemia: A Possible Therapeutic Role

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) is the main cause of mortality among hematologic diseases in Western nations. B-CLL is correlated with an intense alteration of the immune system. The altered functions of innate immune elements and adaptive immune factors are interconnected in B-CLL and are decisive for its onset, evolution, and therapeutic response. Modifications in the cytokine balance could support the growth of the leukemic clone via a modulation of cellular proliferation and apoptosis, as some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 225 publications
2
30
0
Order By: Relevance
“…The roles assigned to these example cytokines in the micro-environmental dialogue partially explain the compiled alterations in the blood levels of the corresponding cytokines owing to CLL and their normalization upon treatment with the BTK inhibitor ibrutinib. Finally, our commentary may support informed judgement on the article by Allegra et al [ 1 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The roles assigned to these example cytokines in the micro-environmental dialogue partially explain the compiled alterations in the blood levels of the corresponding cytokines owing to CLL and their normalization upon treatment with the BTK inhibitor ibrutinib. Finally, our commentary may support informed judgement on the article by Allegra et al [ 1 ].…”
Section: Discussionsupporting
confidence: 66%
“…Enhancing a recent review article published in this journal [ 1 ], the present discussion of paracrine interactions in the B cell lymphoma microenvironment emanates from evidence gained with in vitro cultures of different cell types. The chemokines CCL3 and CXCL12 represent contrasting examples of induced and constitutive production by tumor and bystander cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al ( 20 ) reported that the degree of lymphopenia and the severity of proinflammatory cytokine storms are increased in severe COVID-19 patients compared with those in patients with mild cases. Severe patients showed significant and sustained decreases in lymphocyte and T-cell counts and increases in IL-6, IL-10, IL-2, and IFN-γ levels, while mild cases exhibited increased neutrophil counts ( 12 , 21 ). The clinical characteristics in our case were consistent with the features of severe cases.…”
Section: Discussionmentioning
confidence: 99%